1995
DOI: 10.1080/07924259.1995.9672452
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative data about gametogenesis and embryonic development inHydra vulgarisPall. (Cnidaria, Hydrozoa)

Abstract: This paper reports on the reproductive behavior of gametogenically active polyps of Hydra vulgaris (Pallas, 1766) strain "Scotland 1989" covering an observation period of 4 years . The monitored sexually active hermaphrodites and all their asexually generated offspring produced gametes in uninterrupted series of individual sexual periods, which did not exclude reproduction by budding. Quantitative data are given about the investments made by polyps into gametogenesis in the course of a sexual period. A growing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The oral-aboral distribution of Balanophyllia europaea gametogenetic processes is in some ways analogous to that found in other hermaphroditic polyps of freshwater hydras (Stagni 1974, Vannini 1974, Grassi et al 1995, the octocoral Heteroxenia fuscenses (Achituv & Benayahu 1990) and the scleractinian corals Stylophora pistillata (Rinkevich & Loya 1979) and Oulastrea crispata (Lam 2000). Freshwater hydrozoans, and anthozoans, are characterized by the presence of nervous cells throughout their entire body; it has been hypothesized that the neurosecretory activity of these cells is responsible for determining the sexual gonad distribution along the polyp's oral-aboral axis (Schaller 1973, Schaller & Gierer 1973, Stagni 1974).…”
Section: Oral-aboral Distribution Of Gametogenic Processesmentioning
confidence: 84%
“…The oral-aboral distribution of Balanophyllia europaea gametogenetic processes is in some ways analogous to that found in other hermaphroditic polyps of freshwater hydras (Stagni 1974, Vannini 1974, Grassi et al 1995, the octocoral Heteroxenia fuscenses (Achituv & Benayahu 1990) and the scleractinian corals Stylophora pistillata (Rinkevich & Loya 1979) and Oulastrea crispata (Lam 2000). Freshwater hydrozoans, and anthozoans, are characterized by the presence of nervous cells throughout their entire body; it has been hypothesized that the neurosecretory activity of these cells is responsible for determining the sexual gonad distribution along the polyp's oral-aboral axis (Schaller 1973, Schaller & Gierer 1973, Stagni 1974).…”
Section: Oral-aboral Distribution Of Gametogenic Processesmentioning
confidence: 84%
“…This allows for sex change even in the presence of a male repressive signal and led to the establishment of sequential hermaphroditic phenotypes. Yet, a few Hydra vulgaris strains have been reported that resemble simultaneous hermaphrodites (Grassi et al, ), indicating that sequential hermaphroditism may have been secondarily lost. These models for Hydra phenotypic sex switching provide a framework for future experimentation.…”
Section: Sex Determination In Hydrozoansmentioning
confidence: 99%